Green Synthesis of Copper Nanoparticles Using Boerhaavia diffusa: Evaluation of Cytotoxic and Anti-Diabetic Activities - Vennila Mahendran, Kayal; Rajan KV, Ranjeth; Priyadarshini, Priyadarshini; R., Ramesh. (Journal of Neonatal Surgery, 2025)
Background: Traditional nanoparticle synthesis methods often involve toxic chemicals, posing risks to the environment and human health. Green synthesis using plant extracts offers a sustainable and eco-friendly alternative. Boerhaavia diffusa, a medicinal herb, is rich in bioactive compounds and has potential for producing biocompatible nanoparticles with therapeutic applications. Aim: To synthesize copper nanoparticles (CuNPs) using Boerhaavia diffusa extract and evaluate their cytotoxic and anti-diabetic activities. Materials and Methods: Boerhaavia diffusa leaves were processed to obtain an extract used as a reducing and stabilizing agent for synthesizing CuNPs. The cytotoxicity of the nanoparticles was tested using brine shrimp assays at varying concentrations, while their anti-diabetic activity was assessed through α-amylase inhibition and DPPH assays. Statistical analysis was performed using the Shapiro-Wilk test for data normality, the Kruskal-Wallis test for group comparisons, and Spearman’s rank correlation to evaluate relationships between concentration and observed effects. Results: CuNP synthesis was confirmed by a color transition and UV-Vis spectroscopy. Cytotoxicity assays revealed survival rates of 70–100%, indicating low toxicity. Anti-diabetic assays demonstrated effective α-amylase inhibition and free radical scavenging. Statistical analysis confirmed significant dose-dependent cytotoxicity and wavelength-dependent absorbance properties. Conclusion: Boerhaavia diffusa-mediated CuNPs are biocompatible and exhibit promising therapeutic potential, particularly for anti-diabetic applications, highlighting the feasibility of green synthesis for nanomedicine development.